Comprehensive characterization of skeletal tissue growth anomalies of the finger coral Porites compressa - Domart-Coulon, I; Traylor-Knowles, N; Peters, E; Elbert, D; Downs, C; Price, K; Stubbs, J; McLaughlin, S; Cox, E; Aeby, G; Brown, P; Ostrander, G (2006)
The scleractinian finger coral Porites compressa has been documented to develop raised growth anomalies of unknown origin, commonly referred to as "tumors". These skeletal tissue anomalies (STAs) are circumscribed nodule-like areas of enlarged skeleton and tissue with fewer polyps and zooxanthellae than adjacent tissue. A field survey of the STA prevalence in Oahu, Kaneohe Bay, Hawaii, was complemented by laboratory analysis to reveal biochemical, histological and skeletal differences between anomalous and reference tissue. MutY, Hsp90a1, GRP75 and metallothionein, proteins known to be up-regulated in hyperplastic tissues, were over expressed in the STAs compared to adjacent normal-appearing and reference tissues. Histological analysis was further accompanied by elemental and micro-structural analyses of skeleton. Anomalous skeleton was of similar aragonite composition to adjacent skeleton but more porous as evidenced by an increased rate of vertical extension without thickening. Polyp structure was retained throughout the lesion, but abnormal polyps were hypertrophied, with increased mass of aboral tissue lining the skeleton, and thickened areas of skeletogenic calicoblastic epithelium along the basal floor. The latter were highly metabolically active and infiltrated with chromophore cells. These observations qualify the STAs as hyperplasia and are the first report in poritid corals of chromophore infiltration processes in active calicoblastic epithelium areas. © 2006 Springer-Verlag.